Cost reduction of hotdog formulation - Tingson, Ma. Lourdes
Beef hearts and Textured Vegetable Protein (TVP) were substituted for beef to reduce production costs of hotdogs. Beef was substituted by 5 and 10% of TVP and 50 and 100% beef hearts. The products were evaluated for their eating quality and physico-chemical characteristics. Color of the samples varied, with those containing 100% beef hearts being the darkest, followed by 50% hearts, then by the control, then by the 5% soy and lastly by the 10% soy. Hotdogs with 100% hearts were the most tender, followed by the 10% soy, 50% hearts, and the control was the least tender. Statistical analyses of the sensory evaluation showed significant differences among treatments for texture, juiciness, and general acceptability but no significant difference for flavor strength. ranking of the samples showed that samples with 50% hearts were the most preferred. Statistical analysis of the rank scores by the Kramer Rank Sum Test reveal that there was no significant difference among the samples, except the control, which was rated as the least superior.